KETERSEDIAN KOLEKSI MUATAN LOKAL DALAM MENINGKATKAN LITERASI INFORMASI MASYARAKAT TENTANG KEARIFAN LOKAL DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PADANG PANJANG - Sri Wulandari Martinus (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
The purpose of this study is to describe (1) the availability of collections local content in increasing public information literacy about wisdom local at the Padang Panjang City Library and Archives Service; (2) obstacles in improving public information literacy about local wisdom in the Dinas Padang Panjang City Library and Archives; and (3) efforts in improving public information literacy about local wisdom in the Dinas Padang Panjang City Library and Archives. This research is a type of qualitative research with a descriptive method. Data collection techniques through observation, interview, and documentation. Research data was obtained from the results of an interview with the Head of the Library Service and Assistant Service Staff Padang Panjang City Library and Archives. The results of this study are as follows. First, in doing availability of local library collections pay attention to indicators availability of library collections including. (1) relevance, availability collection of local content in the library is relevant to the related user needs collection of local content; (2) user-oriented, collection availability local content in the library related to the information needs of users; (3) completeness of collections, completeness of local content collections in the library is still not complete because it only exists in printed form; (4) the ratio of titles, users and field specialist. The ratio between the titles of local content collections in the library and current users is still limited; (5) does not conflict with politics, ideology, religion or belief, race, or class. Availability of local content collection what is in the library does not conflict with politics, ideology, religion as well as existing races and groups; (6) scientific objects, collection availability local content in the library is adjusted to the vision and mission of the parent institution to achieve goals and objectives. Second, the City Library and Archives Service Padang Panjang has obstacles, namely: (1) lack of librarians functional in carrying out coaching activities; (2) users looking for local content collection is still very limited; (3) lack of active community participation. Third, the Padang Panjang City Library and Archives Service carried out several efforts to improve public information literacy about wisdom local Padang Panjang, namely: (1) holding traditional training activities; and (2) providing guidance to the Community Reading Park (TBM)